2015
DOI: 10.1186/s13019-015-0363-1
|View full text |Cite
|
Sign up to set email alerts
|

Management of patients with flail chest by surgical fixation using claw-type titanium plate

Abstract: BackgroundThe goal of the study was to compare surgical rib fixation using claw-type titanium plate with conservative treatment in the management of patients with flail chest.MethodsThe study retrospectively studied 23 patients suffering from flail chest injury, who admitted to our hospital from October, 2010 to February, 2014. The patients received surgical fixation by using claw-type titanium plate (surgical fixation group). A age and sex-matched cohort of 29 patients received conservative treatment and defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Nine studies ( n = 1174) reported on implant removal; five studies reported zero events and four studies reported implant removal ranging from 1.5 to 4.9% (Online Appendix 4) [17, 26, 28, 3638, 40, 45, 48]. Eleven studies reported on wound infection; five studies reported zero events and six studies reported a wound infection rate ranging from 1.7 to 25% [18, 23, 24, 2630, 46]. Other short and/or long-term complications were poorly reported and described mainly respiratory complications.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies ( n = 1174) reported on implant removal; five studies reported zero events and four studies reported implant removal ranging from 1.5 to 4.9% (Online Appendix 4) [17, 26, 28, 3638, 40, 45, 48]. Eleven studies reported on wound infection; five studies reported zero events and six studies reported a wound infection rate ranging from 1.7 to 25% [18, 23, 24, 2630, 46]. Other short and/or long-term complications were poorly reported and described mainly respiratory complications.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies show a mean duration of ICU stay of 14 days for patients who had nonoperative treatment for a flail chest with an SD of 4.5 19 20. To detect 3 days difference in ICU stay with a power of 80% and two-sided alpha of 0.05, accounting for 15% loss after propensity score (PS) matching, the total number of patients needed is approximately 82.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Flail chest is among the most severe chest wall injuries. A flail chest is defined as three or more consecutive rib fractures, in two or more places, creating a flail segment [3,4]. This is the most severe form of rib fractures and this injury is associated with significant morbidity and mortality rates [5].…”
Section: Introductionmentioning
confidence: 99%